Gender perspective in the labor and social protection discipline. Foundations and limits - Puebla, Ana de la (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
The gender perspective, as conceived in international instruments and national norms, has a general and interdisciplinary projection. Undoubtedly, the need for this perspective as a criterion of judicial resolution is particularly significant in the social sphere, for reasons linked to the very configuration of social norms and the sociological and temporal context in which they are elaborated. In this regard, the courts of the social jurisdiction have been applying the hermeneutic criterion of the gender perspective in numerous judicial decisions, especially those related to social protection, to correct interpretations of norms that deepen gender-based discrimination. Recent pronouncements, however, bring to the forefront the possibility of setting limits to the application of the gender perspective canon, warning about the necessary distinction between the creative and interpretative function that corresponds to the judicial bodies.